Anti-inflammatory new cyathane diterpene glucosides from Onychium japonicum. (August 2021) - Zan, Ke; Gan, Yongqiang; Xie, Peide; Zhang, Ronglin; Ma, Shuangcheng; Lin, Queyue; Zheng, Jian
Graphical abstract: Highlights: Cyathane diterpene glucosides from Onychium japonicum were explored. Two new compounds were isolated. Their structures were elucidated based on spectroscopic evidence. Inhibitory activity against LPS-induced nitric oxide production was investigated. Abstract: The chemical exploration of Onychium japonicum (Thunb.) O. Kuntze (Pteridaceae) aerial parts afforded two new cyathane diterpene glucosides (1 and 2) . The structure elucidation of the new compounds was unambiguously performed based on HRESIMS and 1D and 2D NMR spectroscopic data analyses. These two compounds represent the first two cyathane diterpenes with a glucopyranosyl moiety. Compounds 1 and 2 exhibited potent inhibitory effects against LPS-induced nitric oxide (NO) production in RAW246.7 macrophages with its IC50 values of 1.76 and 2.82 μM, respectively.